Extinction Cross-Section Modeling of Metallic Nanoparticles - Hussain, Firas Faeq. K.; Mansoor, Riyadh; Hussein, Rasha A. (Iraqi Journal of Science, 2020)
Localized surface plasmons (LSPs) are a potentially valuable property for the practical use of small size metallic particles. Exploiting the LSPs in metallic nanoparticle (NP)-based solar cells was shown to increase the efficiency of solar panels. A large extinction cross section of NPs allows for high scattering of light at the surface of the panel, which reduces the panel thickness, allowing for small size and low-cost solar cells. In this paper, the extinction cross-section of spherical nanoparticles is studied and simulated numerically. Surface plasmons were first modeled using the Drude’s model then the scattering and absorption cross-sections were derived. Commercial3D simulation software was used to model the near field distribution of the three NP structures. A spherical nanoparticle made of silver was modeled first and the field distribution inside the sphere was presented. The extinction cross-section was also calculated. Two other structures were also presented; a silica NP was first coated with silver shell then a silver NP was coated with silica shell. These structures were studied to estimate the effects of the surroundings on the extinction cross-section. The results show that the silica NP coated with a silver shell provides a high extinction cross-section and can be considered as a good choice for the LSPs-based solar cells.